Phenolic content and in vitro bioactivities of Chinese Potato (Plectranthus rotundifolius) tuber extracts - Megha Madhavan; V.R.Vishnu; S. Shanavas; Jyothi, Dr A N (JOURNAL OF ROOT CROPS, 2023)
Plectranthus rotundifolius, commonly known as Chinese potato in India, is a perennial herbaceous plant of the Mint family Lamiaceae and is native to the tropical Africa. These are found to be rich in nutrients and have great medicinal properties. The tubers contain several secondary metabolites that are of therapeutic and pharmaceutical importance. The tubers in the dry and cooked form were analysed for the phenolic content and the in vitro bioactivities including antioxidant, anti-inflammatory and antidiabetic activities by various biochemical assays. The tubers were also subjected to cooking to find out its effect on the phenolic content and antioxidant activities. The study revealed that cooked tubers have greater phenolic content and antioxidant, anti-inflammatory and antidiabetic activities than the raw tubers and it indicates that cooked form of tuber is better to consume than the raw tuber.